2
$\begingroup$

For 1-d Gaussian quadrature with two points per element we have the following formula to transform an integral from an arbitrary domain $[a, b]$ to the reference domain $[-1,1]$ on which various Gaussian quadrature formulas for weights node points are defined -

$$\int_a^b f(x) dx \approx \frac{b-a}{2}\sum_{i=1}^n w_i f(\frac{b-a}{2}x_i + \frac{a+b}{2})$$

where, in the case of $n = 2$ points we have $x_i = \pm \frac{1}{\sqrt{3}}$ and $w_i = 1$. See Gaussian Quadrature

Now I am wondering what is the equivalent transformation if our reference domain is $[0,1]$ instead of $[-1,1]$. We will obviously have to change the transformation that gets applied to $x_i$ and the scaling factor outside the integral. Do we also have to transform the weights?

$\endgroup$

2 Answers 2

3
$\begingroup$

Yes, we do have to transform the weights.

Consider first the mapping from $[-1,1]$ to $[a,b]$, that is, $$ g_1(\widehat{x})=\frac{b-a}{2}\widehat{x}+\frac{b+a}{2}, $$ which clearly satisfies $g_1(-1)=a$ and $g_1(1)=b$. Then by the change of variables $$ \int_a^b f(x)\,\mathrm{d}x = \int_{-1}^1 f(g_1(\widehat{x}))\frac{b-a}{2}\,\mathrm{d}\widehat{x} = \frac{b-a}{2}\int_{-1}^1 f(g_1(\widehat{x}))\,\mathrm{d}\widehat{x}, $$ where the integral on the right hand side can be computed using the quadrature rule $$ \int_{-1}^1 f(g_1(\widehat{x}))\,\mathrm{d}\widehat{x} = \sum_{i=1}^n \widehat{w}_i f(g_1(\widehat{x}_i)) $$ with some points $\widehat{x}_i \in [0,1]$ and weights $\widehat{w}_i$, $i \in \{1,\cdots,n\}$.

Next consider the mapping from $[0,1]$ to $[a,b]$, that is, $$ g_2(\widetilde{x})=(b-a)\widetilde{x}+a, $$ which satisfies $g_2(0)=a$ and $g_2(1)=b$. Similarly as before $$ \int_a^b f(x)\,\mathrm{d}x = \int_0^1 f(g_2(\widetilde{x}))(b-a)\,\mathrm{d}\widetilde{x} = (b-a)\int_0^1 f(g_2(\widetilde{x}))\,\mathrm{d}\widetilde{x}, $$ and $$ \int_0^1 f(g_2(\widetilde{x}))\,\mathrm{d}\widetilde{x}=\sum_{i=1}^n \widetilde{w}_i f(g_2(\widetilde{x}_i)) $$ for some other points $\widetilde{x}_i \in [0,1]$ and weights $\widetilde{w}_i$, $i \in \{1,\cdots,n\}$.

Combining some of the previous equations we get $$ (b-a)\int_0^1 f(g_2(\widetilde{x}))\,\mathrm{d}\widetilde{x}=\frac{b-a}{2}\int_{-1}^1 f(g_1(\widehat{x}))\,\mathrm{d}\widehat{x} $$ or, equivalently, $$ \sum_{i=1}^n \widetilde{w}_i f(g_2(\widetilde{x}_i)) = \frac{1}{2} \sum_{i=1}^n \widehat{w}_i f(g_1(\widehat{x}_i)). $$ This holds true if $$ \widetilde{w}_i = \frac{\widehat{w}_i}{2} $$ and $$ (b-a)\widetilde{x}_i+a = \frac{b-a}{2}\widehat{x}_i+\frac{b+a}{2} \Rightarrow \widetilde{x}_i = \frac{1}{2}\widehat{x}_i+\frac{1}{2} $$ for every $i\in\{1,\cdots,n\}$. In conclusion, we can get the quadrature $(\widetilde{x}_i,\widetilde{w}_i)$ for the domain $[0,1]$ from the quadrature $(\widehat{x}_i,\widehat{w}_i)$ for the domain $[-1,1]$ by using the formulae $$ \left\{ \begin{aligned} \widetilde{w}_i &= \frac{\widehat{w}_i}{2}, \\ \widetilde{x}_i &= \frac{1}{2}\widehat{x}_i+\frac{1}{2}. \end{aligned} \right. $$

$\endgroup$
1
$\begingroup$

Here me out, we already have a table for solvable values on [-1,1], we can adjust the range by doing +1 to get [0,2], then do /2 to get [0,1]. Why not modify our xi and wi with the above steps to get the new domain instead of modifying our function...

$\endgroup$
1
  • 1
    $\begingroup$ As it’s currently written, your answer is unclear. Please edit to add additional details that will help others understand how this addresses the question asked. You can find more information on how to write good answers in the help center. $\endgroup$
    – Community Bot
    Jul 30, 2022 at 23:20

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .